An experimental study of brand signal quality of products in an asymmetric information environment. - Tsao, Hsiu-Yuan (Curtin University, 2002)
Previous research regarding the effectiveness of signalling via brand name has focused on when and how any brand-building cost incurred, will be rewarded by future profit. In contrast to this seller-incentive perspective, this study examines how the buyer interprets the signal via brand name, the effectiveness of signalling via brand name in terms of buyer value perspective, and how the buyer's reaction toward the signal impacts on the seller's decision to adopt the signalling strategy. Signalling theory and concepts from consumer-based branding research are used to suggest how to evaluate the effectiveness of signalling via brand name in the context of the consumer market, wherein information is asymmetric. Findings from online trading experiments, using the methodology of experimental economics, demonstrate that the function of brand fluctuates according to which market conditions prevail for brand and price, the extent of brand differentiation, and the magnitude of brand-building cost. This suggests an alternative way to measure the value of a brand to the buyer.